2006
DOI: 10.1021/es060301u
|View full text |Cite
|
Sign up to set email alerts
|

Levels of 12 Perfluorinated Chemicals in Pooled Australian Serum, Collected 2002−2003, in Relation to Age, Gender, and Region

Abstract: Pooled serum samples from 3802 Australian residents were analyzed for four perfluoroalkylsulfonates, seven perfluoroalkylcarboxylates, and perfluorooctanesulfonamide (PFOSA). Serum was collected from men and women of five different age groups and from rural and urban regions in Australia. The highest mean concentration was obtained for perfluorooctane sulfonate (PFOS, 20.8 ng/mL) followed by perfluorooctanoic acid (PFOA, 7.6 ng/mL), perfluorohexane sulfonate (PFHxS, 6.2 ng/mL), perfluorononanoic acid (PFNA, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
88
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(101 citation statements)
references
References 32 publications
11
88
2
Order By: Relevance
“…There is limited information about human PFC concentrations in the southern hemisphere. Two human studies from Australia 25,29 reported PFC concentrations that were comparable to the northern hemisphere, and in one study from Brazil, the concentrations were 5-10 times lower than levels found in the sera of donors in the United States.…”
mentioning
confidence: 95%
“…There is limited information about human PFC concentrations in the southern hemisphere. Two human studies from Australia 25,29 reported PFC concentrations that were comparable to the northern hemisphere, and in one study from Brazil, the concentrations were 5-10 times lower than levels found in the sera of donors in the United States.…”
mentioning
confidence: 95%
“…[11][12][13][14][15] These findings suggest that general population is exposed to such perfluorochemicals which have globally spread at very low levels.…”
mentioning
confidence: 95%
“…The reaction mixture was then applied to high-performance liquid chromatography using a reverse-phase column (YMC-Pack pro, 4.6ϫ50 mm, YMC, Kyoto, Japan). The fraction containing p-bromophenacyl derivative of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]PFOA was collected and was taken to dryness by flushing nitrogen, and p-bromophenacyl derivative of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]PFOA was hydrolyzed with 10% (w/v) KOH/90% methanol (v/v) at 80°C for 60 min. After being neutralized with 6 M HCl, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]PFOA was extracted with ethyl acetate : hexane (1 : 1, v/v) as an ion pair with tetrabutylammonium in the presence of 0.29 M NaCO 3 buffer (pH 10.0).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these features, PFCs are widely applied in industrial and agricultural production and domestic use. Perfluorooctanoic acid (PFOA), a representative PFC, is used not only in conventional industries such as the chemical industry, leather and textiles, machinery, and medicines, but also in high-technology industries such as aviation and aerospace, semiconductors, microelectronics, and the military (Kärrman et al, 2006;Chen et al, 2009). However, PFOA poses a considerable threat to human health and the environment because of its persistence, bioaccumulation, carcinogenicity, teratogenicity, mutagenicity, and endocrine disruption activity (So et al, 2004;Luebker et al, 2005;Grasty et al, 2005;Prevedouros et al, 2006).…”
Section: Introductionmentioning
confidence: 99%